2018
DOI: 10.1016/j.yebeh.2018.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy misconceptions and stigma reduction interventions in sub-Saharan Africa, a systematic review

Abstract: Epilepsy misconceptions, stigmatizing cultural beliefs, and perceptions were widely prevalent in SSA, and there are a few studies targeting epilepsy stigma. Existing stigma-reduction educational approaches may be impractical for general population implementation. Scalable approaches to reduce stigma are urgently needed within SSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 37 publications
(76 reference statements)
3
60
0
Order By: Relevance
“…7 Our cohort of 235 patients had a broad age distribution, ranging from 1-to 78-years-old, with a substantial proportion younger than 20 years: up to 42% of the children included in our study were younger than10 years old and 24% were even younger than 2 years. [17][18][19] Several findings point to stigmatization of PwE. Indeed, limited information is available on the etiology and exact diagnosis of seizure type or syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Our cohort of 235 patients had a broad age distribution, ranging from 1-to 78-years-old, with a substantial proportion younger than 20 years: up to 42% of the children included in our study were younger than10 years old and 24% were even younger than 2 years. [17][18][19] Several findings point to stigmatization of PwE. Indeed, limited information is available on the etiology and exact diagnosis of seizure type or syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether this is due to stigma or cognitive decline in our patients. [17][18][19] Several findings point to stigmatization of PwE. Sebera et al 20 reported in 2005 that more than two-thirds of the Rwandan population considered PwE not apt to get married.…”
Section: Discussionmentioning
confidence: 99%
“…Misconception is a complex social construction with all the associated consequences that could explain, at least partially, unequal opportunities in employment and education for PWE [42]. In an effort to determine the factors associated to epilepsy misconception in sub-Saharan Africa, a systematic review found that perceptions of how epilepsy affects people with epilepsy were significantly associated with rural residence, the male sex, and lower education [43].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other women in SSA, fewer WWE go for antenatal visits [23]. This might be related to their relatively lower economic status, to the fact that some of them may be cognitively impaired, or as a result of the prevailing stigma by the community and to a lesser extent among healthcare personnel [58]. WWE and their families should be educated on the benefits of following up their pregnancy at the local Table 2 Comparison of the benefits and disadvantages of AEDs used in women with epilepsy.…”
Section: Antenatal and Post-natal Follow-upmentioning
confidence: 99%